Influence of transformational leadership, spiritual leadership and technology innovation on organizational effectiveness of universities in Pakistan - Ahmad, Sajjad (2020)
The aim of this study is to examine how the effectiveness of Pakistani universities can be enhanced through transformational and spiritual leadership and to what extent technology innovation intervenes in this relationship. The Upper Echelons Theory (UET) underpins the research framework. A cross-sectional survey was employed through a self-administered questionnaire for data collection from a sample of 389 academic and managerial employees of 21 Pakistani universities. PLS-SEM with path modeling and bootstrapping was utilized to examine the effect of the two leadership styles on organizational effectiveness, mediated by technology innovation. Seven out of eight hypotheses were accepted while only one was rejected. The study results significantly contributed to the literature; First, by testing two theories, UET and STS, with data from the new sector, and new geographical context. Second, it examined the impact of leadership style on organizational effectiveness with a moderated mediated model. Third, it provided practical implications for strategists and decision-makers in higher education. Practical suggestions were provided at the end of the study, and importance-performance map analysis (IPMA) was conducted to support the managerial implications of the study results empirically.